Characterisation and diversity of Indian isolates of Ralstonia solanacearum causing bacterial wilt of Capsicum annuum L. (3rd April 2018) - Singh, Dinesh; Chaudhary, Garima; Yadav, D. K.
Abstract: Genetic diversity of 13 isolates of Ralstonia solanacearum causing bacterial wilt in hot pepper and bell pepper ( Capsicum annuum L.) from 6 states of India was assessed. All isolates of R. solanacearum belonged to biovar 3, race 1 and phylotype I. These isolates consisted of 4 distinct DNA types at 75% similarity coefficient using ERIC, BOX and REP-PCRs techniques. Multilocus sequence analysis of hrp B, fliC and egl genes of 6 isolates of R. solanacearum along with 2 out group bacteria was done and they showed high level of variability within these three regions of the genome involving in pathogenicity.